ANALISIS STRATEGI PEMASARAN PADA UMKM RUMAOS STORE DI DESA SUDALARANG KECAMATAN SUKAWENING KABUPATEN GARUT JAWA BARAT - Nadiatun Nisa, Anida (EKSYDA: Jurnal Studi Ekonomi Syariah, 2025)
Abstract The purpose of this research is to determine marketing strategies to increase t-shirt sales at the Rumaos Sudalarang Sukawening Garut store. This research was conducted using a qualitative descriptive approach. Interview and documentary techniques were used for data collection. The research results show that the Rumaos store marketing strategy is quite successful and can increase the level of sales volume based on indicators, product strategy, pricing strategy, distribution channel strategy and advertising strategy. Meanwhile, the growth in sales of Toko Rumaos clothing is known to have greatly increased sales, considering the rapid development of the business and the success of the marketing process, which cannot be separated from the metrics: the conditions and skills of the sellers. , market conditions, capital and company organizational conditions.